Teachers’ Efforts to Boost Students’ Motivation and Interest in History at Balaesang State High School No. 2 - Ayu Inda Lestari; Misnah Misnah; Mahfud M. Gamar; Minarni Nongtji (Journal of Educational Sciences, 2026)
This study aims to examine the efforts of history teachers to increase students’ motivation and interest in learning history at Balaesang State Senior High School 2. The study employed a qualitative approach involving the school principal, two history teachers, and eight students as research participants. Data were collected through observation, interviews, and documentation, then analyzed using the Miles, Huberman, and Saldaña model, which includes data reduction, data presentation, and conclusion drawing. The findings indicate that students’ motivation and interest in learning history were generally in the moderate category. Learning motivation was reflected in students’ participation in discussions, willingness to ask questions, attention during lessons, and responsibility in completing assignments. Meanwhile, learning interest was evident in students’ enthusiasm for classroom activities, involvement in group work, and curiosity about historical topics. While some students viewed history as important for understanding past events and national values, others still perceived it as a subject dominated by memorization. To address these challenges, teachers implemented various instructional strategies, including discussions, presentations, question-and-answer sessions, debates, and project-based assignments. They also utilized visual media and educational technology, such as documentary videos and PowerPoint presentations, to make lessons more engaging and easier to understand. These efforts contributed to increased student participation, engagement, and understanding of historical material.